Pengaruh Pemberian Pupuk Bokashi Terhadap Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L) - Hari, Jenike Mariani; Killa, Yonce Melyanus (Prodi Agroteknologi dan Agribisnis - Universitas Kristen Wira Wacana Sumba, 2024)
Mustard greens are the most popular plants in the community and are rich in nutritional sources. Increasing mustard greens production can be increased by increasing the availability of nutrients in the soil through the provision of bokashi fertilizer. The purpose of this study was to determine the effect of bokashi fertilizer on the growth and yield of mustard greens. This research was conducted in a plastic house in Padadita, Prailiu Village, Kambera District, East Sumba Regency. This research was conducted from June - July 2024. This research was designed using a completely randomized design (CRD) consisting of 5 treatments with 4 replications. So there are 20 experimental units. The treatments tested were: P0 (without fertilizer), P1 (5 tons of bokashi/ha), P2 (10 tons of bokashi fertilizer/ha), P3 (15 tons of bokashi fertilizer/ha), P4 (20 tons of bokashi fertilizer/ha). The observation variables in the study were plant height, number of leaves, leaf length, and wet weight. The data were analyzed statistically with the F Test, then a further test was carried out by Duncan's New Multiple Range Test (DNMRT) at a significant level of 5%. Based on the results of the study, it showed that the bokashi dose fertilizer made from sawdust, goat feces, gamal leaves and rice washing water had a significant effect on the height of mustard greens, the longest leaves were found in the 2nd and 3rd weeks of observation and the wet weight of mustard greens. The best treatment that gave an effect was P1 (5 tons / ha) with the highest value.